An investigation of unsuccessful performance and subsequent retake behavior in principles of economics. (23rd November 2022) - Emerson, Tisha L. N.; McGoldrick, KimMarie
Abstract: Using student transcript data from eight institutions over 23‐years, we investigate enrollments in principles of microeconomics to determine characteristics of successful and unsuccessful students. We follow unsuccessful students to identify determinants of retake decisions and success (or lack thereof) for repeaters. Higher aptitude and more senior students are more likely to succeed in microeconomic principles. Experience with macroeconomics principles, financial accounting, and calculus also increases the likelihood of success. Traditionally challenged groups (females and underrepresented minorities) are more likely to be unsuccessful. Unsuccessful students who complete the course (earning less than a C‐) differ from withdrawers. Academically stronger females and URM students are more likely to withdraw than unsuccessfully persist compared to their white, male counterparts. Students with backgrounds in economics or financial accounting are less likely to withdraw. Withdrawers on the first attempt are more likely to retake the course than unsuccessful completers. Academically stronger females are more likely to retake but academically stronger URM students are less likely to do so. Many of the determinants of success, unsuccessful completion, and withdrawal from the first attempt remain significant predictors of outcomes for repeaters. We conclude with policy suggestions.